Inhibition of bacterial growth of Leilem leaf extract (Clerodendrum minhassae Teijsm. & Binn): Inhibition of bacterial growth of Leilem leaf extract - Masje Wurarah; Yermia Semuel Mokosuli (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2022)
Leilem (Clerodendrum minhassae Teism. & Binn.) is a plant endemic to Sulawesi. Leilem leaves are used as a typical food vegetable for the Minahasa tribe. However, leilem leaves were used as a medicinal plant for intestinal worms, abdominal pain and chest pain. There has been no research report on the use of leilem leaves as a source of antibacterial bioactivity. This study aims to obtain the best concentration of antibacterial Leilem leaf extract. Leilem leaves are obtained from North Minahasa. Extraction by maceration method using various solvents with a level of polarity. The test concentrations of the extract were 100 mg/L, 200 mg/L, 400 mg/L and 800 mg/L. As a positive control, clindamycin 400 mg/L was used. The results showed that the percentage of solvent yield was ethanol, which was 1.23% at 1:4 (w/v) maceration. The average diameter of bacterial growth is 12.6 mm. The results of the one way ANOVA analysis showed significant differences between test concentrations (p>0.5). Tukey's test showed that the three extracts significantly inhibited the growth of gram-positive bacteria Staphylococcus aureus strain ATCC 25923. The n-hexane extract showed the best antibacterial activity, followed by ethanol extract and ethyl acetate extract. Leilem leaves are potential to be developed as a source of antibacterial bioactive.